Penyusunan Basis Data Infrastruktur Sanitasi Sekolah Dasar Negeri Berbasis Website di Kecamatan Rasau Jaya - Reza Wahyudi; Ridho Dedy Arief Budiman; Farly Detrias (Fakultas Teknik, 2020)
The compilation of a database of public primary school sanitation infrastructure in Rasau Jaya District is based on the 2007 Minister of Education Regulation on the standards for facilities and infrastructure of public primary schools in Indonesia. Besides, this research is also an effort to support the Kubu Raya District one data program which aims to help district governments in planning district programs so that they can be implemented properly and accurately in the field of public elementary school sanitation infrastructure. In this study direct observations to the site and conduct interviews related to the availability of primary school sanitation infrastructure. The number of public elementary schools included in the research area is 18 public elementary schools spread across 6 villages in Rasau Jaya District. The results of this study are in the form of a website-based elementary school sanitation infrastructure database which can be viewed on the website www.sigsanitasikuburaya.com. On the website, data can be seen including the availability of handwashing facilities, latrine facilities, clean water facilities, menstrual facilities, waste management facilities, and drainage facilities.